The Impact of Teaching Factory and Industry Partnership on Work Readiness and Employability of Graduates from the Spa and Beauty Expertise Program at SMKN 2 Singaraja, Bali - Dharmayanti, Ni Made Lia; Suhartini, Ratna; Rijanto, Tri (Journal of Vocational Education Studies, 2025)
The Ministry of Education, Culture, Research, and Technology aims to improve Human Resources (HR) quality through the implementation of teaching factories. The teaching factory improves work readiness and increases graduate employment rates. This study aims to: 1) assess the impact of teaching factories on work readiness; 2) evaluate the effect of teaching factories on graduate absorption; 3) examine the influence of industry partnerships on job readiness; 4) explore the effect of industry partnerships on graduate absorption; 5) investigate the relationship between job readiness and graduate absorption; 6) determine the role of teaching factories in graduate absorption through job readiness; and 7) assess the influence of industry partnerships on graduate absorption via work readiness in the Spa and Beauty Expertise Program. Data was collected using a questionnaire distributed via Google Forms, and path analysis was employed for data analysis. The results indicate that: 1) teaching factories positively affect work readiness (significance value = 0.000, p < 0.05); 2) teaching factories positively influence graduate absorption; 3) industry partnerships positively impact work readiness; 4) industry partnerships positively affect graduate absorption; 5) job readiness contributes positively to graduate absorption; 6) teaching factories enhance graduate absorption through job readiness; and 7) industry partnerships support graduate absorption through student work readiness in the Spa and Beauty Expertise Program.